If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 = 9 + 2u Solving 17 = 9 + 2u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-2u' to each side of the equation. 17 + -2u = 9 + 2u + -2u Combine like terms: 2u + -2u = 0 17 + -2u = 9 + 0 17 + -2u = 9 Add '-17' to each side of the equation. 17 + -17 + -2u = 9 + -17 Combine like terms: 17 + -17 = 0 0 + -2u = 9 + -17 -2u = 9 + -17 Combine like terms: 9 + -17 = -8 -2u = -8 Divide each side by '-2'. u = 4 Simplifying u = 4
| -2+12-(-14)= | | 66w-50= | | 4(2x-3)-3(x-4)+7x=6 | | 77x+20=350 | | x^2+x-1=15x | | -14+23=-3(x+2) | | 2(3z+1)-(z-6)=18 | | -135+2x=52-9x | | .3x-.14x-.81=-.6x+.29 | | 66w+50= | | 9y+15=5y-5 | | X=2x-3+4 | | .3x-.14x-.81=-.6x+29 | | 6x-1=5+3x | | 2*12*40+5*18*40+3238+500= | | 2x-43=65 | | 33w+49-33w+1= | | 9+(-10)= | | 70=-14x | | 0.162+2.76= | | 6x-4+5=1 | | 2+11x+11K-3x-3k-9= | | -44-6n=4(-10-n) | | -8-0-(-16)-7+5= | | 6x^2+25x-24=0 | | 6y-11x=15 | | 15r^2-4r-4=0 | | -4=3b+b | | 2x+3-3x=7 | | (-4+-1x^2)=0 | | (2+5)*(12+18)*40+3238+500= | | .80x+2.30=30 |